Bajiquan martial arts training as physical activity for enhancing physical fitness, body composition, and perceived exercise benefits: a quasi-experimental study - Wang, Chi-Te; Tien, Cheng-Wen; Huang, Wen-Ching (Frontiers in Sports and Active Living, 2025)
BackgroundMartial arts are a traditional aspect of Chinese culture, and with the diverse development of recreational activities, they have gained widespread acceptance not only for self-defense but also as a popular recreational activity. Physical activity and fitness characteristics associated with different martial arts vary depending on developmental backgrounds. Bajiquan is a traditional Chinese martial art known for its explosive power in close combat, emphasizing quick elbow and shoulder strikes over a short range. However, research on the application of Bajiquan to physical activity, health promotion, and its perceived benefits remains relatively limited. This study aimed to investigate the effects of a programmed 8-week Bajiquan training intervention on physical fitness, body composition, and perceived benefits of exercise.MethodsThis quasi-experimental study enrolled participants and allocated them to the experimental (n = 15; 27.4 ± 2.6 years; female = 13.3%) and control groups (n = 15; 26.0 ± 3.1 years; female = 13.3%). The experimental group participated in an 8-week Bajiquan program, whereas the control group engaged in regular exercise with the same intervention frequency. Pre- and post-tests were conducted to assess the effects on physical fitness and body composition. Additionally, participants' subjective perceptions of the benefits of martial arts exercise were evaluated using an exercise perceived benefit questionnaire.ResultsThe experimental group demonstrated significantly higher social relationships (Δ = 17.2%; δ = 0.586, p < 0.05) and personal benefits (Δ = 19.8%; δ = 0.431, p < 0.05) than the control group (p < 0.05). Changes in pre- and post-test measurements within the experimental group were significantly different from those in the control group in terms of body weight (p = 0.008, d = 1.05), body mass index (p = 0.003, d = 1.17), and body fat percentage (p = 0.004, d = 1.13). The experimental group exhibited significant differences in changes in muscle explosive power (p = 0.003, d = 1.27), cardiorespiratory fitness (p = 0.004, d = 1.14), and core muscle strength (p = 0.009, d = 1.10) compared with the control group. Core muscle strength also significantly increased in the experimental group compared to that in the control group in the post-test (Δ = 17.0%; p = 0.003, d = 1.21).ConclusionsThe Bajiquan martial arts exercise intervention demonstrated beneficial effects on physical and mental development, making it a viable option for physical activity programs. In the future, program adjustments and applications can be tailored for different populations, such as children or the elderly, to promote health and disseminate the practice of martial arts.